Acute onset psychiatric diseases after SARS-CoV-2 virus infection among pediatric patients - Yang, Lu; Li, Jun; Zhang, Dongqing (Frontiers in Neurology, 2024)
Background Psychiatric symptoms directly associated with SARS-CoV-2 virus infection have been reported sporadically in children. More cases of new-onset psychosis without severe cardinal symptoms, altered consciousness level, and psychogenic drug usage would offer compelling grounds for the association between the virus infection and psychosis. Methods We collected the clinical data of pediatric patients with new onset psychiatric symptoms after the SARS-CoV-2 virus infection from December 2022 to Feb 2023 and followed up with them for one year. These children did not have severe respiratory, cardiovascular, or systemic symptoms. They were not given psychogenic drugs. We also searched Pubmed to identify previously reported acute onset psychiatric cases related to SARS-CoV-2 virus infection in children. We summarized these patients' clinical symptoms, laboratory examination, treatment, and prognosis. Results We reported eleven new cases of psychiatric disease directly related to SARS-CoV-2 virus infection and reviewed twelve previously reported cases among children and adolescents. They had various psychiatric symptoms within three weeks after the virus infection. Brain MRI and EEG recording did not reveal remarkable abnormalities. The cerebrospinal fluid analysis(CSF) could find increased protein, immunoglobulin, and IL-8 levels, disrupted blood-brain barrier, and positive oligoclonal band in a minority of the patients. Most of the patients had good outcomes. Conclusions New-onset psychiatric symptoms directly related to SARS-CoV-2 virus infection are not rare phenomena among pediatric patients. CSF tests support the presence of central immune responses in some patients. Although these patients received different treatments, most of them had good prognoses.